Harold & Hog Pretend for Real! - Willems, Mo; Santat, Dan (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2019)
Can the friendship of best friends Harold and Hog, a carefree elephant and a careful hog, survive a game of pretending to be Mo Willems's Elephant and Piggie?
Keywords: Swine -- Juvenile fiction; Elephants -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Imagination -- Juvenile fiction; Pigs -- Fiction; Elephants -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Imagination -- Fiction